KOMPREHENSIF PENDIDIKAN TOLERANSI DALAM ISLAM - M Fikar; Ronika Putra; Julhadi; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Tolerance is a fundamental value in Islamic teachings that becomes increasingly relevant in pluralistic societies. However, deviations in the understanding and practice of tolerance still occur due to radicalism, extremism, and low levels of pluralistic awareness. This study aims to comprehensively examine the concept of tolerance in Islam and its role in education as an effort to build an inclusive and moderate character. The method used is normative qualitative research with a library study approach, involving theological, historical, and pedagogical analysis of primary sources such as the Qur’an, Hadith, and Islamic literature. The results show that tolerance in Islam has strong theological foundations, has been practiced since the time of the Prophet, and is highly strategic to be developed through the educational system.